1970
DOI: 10.4141/cjas70-082
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Metabolism in Swine. Interrelationships Between the Level of Energy Intake and Serum Ascorbate Levels

Abstract: The influence of energy intake on serum the serum increased significantly with time in ascorbate levels in swine has been studied. animals fed higher levels of energy, but Dot in There was a significant correlation between animals which recoived lower levels of energy. energy intake and serum ascorbate levels at Th's suggested that energy restriction inage 85-95 days, as well as a significant cor-hibited the development of the capacity to relation between terminal weights and serum synthesize ascorbate. A hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The pigs in this study were exposed to a high environmental temperature due to problems with the ventilation during early spring, which may have contributed to the variations in the vitamin C plasma levels. It has also been suggested that the requirements of vitamin C synthesis are not met during the fast growth of the pigs, and that the level of plasma amino acid is affected by the amount of dietary energy (Brown et al., 1970, 1975; Dvorak, 1974). However, we did not find a significant association between the plasma vitamin C levels and growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…The pigs in this study were exposed to a high environmental temperature due to problems with the ventilation during early spring, which may have contributed to the variations in the vitamin C plasma levels. It has also been suggested that the requirements of vitamin C synthesis are not met during the fast growth of the pigs, and that the level of plasma amino acid is affected by the amount of dietary energy (Brown et al., 1970, 1975; Dvorak, 1974). However, we did not find a significant association between the plasma vitamin C levels and growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…It seems reasonable to suggest that administration of glucose had a favourable effect on A A synthesis in the liver by securing a sufficient supply of the basic pre cursor. In this connection, one may do well to recall the observation of Brown et al [1970] who found a correlation between energy intake and blood serum AA levels in piglets aged 85-95 days. The results obtained in fasted piglets have confirmed that the level of the substrate is an important factor determining the degree of endogenous synthesis of AA.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous synthesis of AA can no doubt be affected by a number of factors in either a positive or negative sense [Chaterjee et al, 1961;Touster and Hollann, 1961;K linger and Ankerman, 1965;DvoftAic, 1967b;Brown et al, 1970]. In this connexion, much consideration has been given to stress [Van Koetsveld, 1968;Coates, 1968].…”
Section: Introductionmentioning
confidence: 99%
“…( I 970) reported that supplementary ascorbic acid at levels up to 440 mg/kg of diet did not produce consistent responses in growth rate or ieed efficiency of swine. On the other hand, stress such as increased environmental temperatures (Riker et al 1967) or decreased energy intake (Brown et al 1970) resulted in depressed serum ascorbic acid levels in swine. Evidence has been presented (Brown et al 1970) to indicate that energy deprivation during the early growth phase prevented a rise in serum ascorbic acid values found in animals fed adequate levels of energy.…”
mentioning
confidence: 99%
“…On the other hand, stress such as increased environmental temperatures (Riker et al 1967) or decreased energy intake (Brown et al 1970) resulted in depressed serum ascorbic acid levels in swine. Evidence has been presented (Brown et al 1970) to indicate that energy deprivation during the early growth phase prevented a rise in serum ascorbic acid values found in animals fed adequate levels of energy. More recently, Dvoi:ik (1974) de-monstrated that ascorbic acid synthesis in young swine was a function of available glucose.…”
mentioning
confidence: 99%